The Dynamics of Disability and Benefit Receipt in Britain - Melanie K. Jones; Duncan McVicar (Institute of Labor Economics (IZA), 2017)
This paper exploits rarely-used longitudinal data to examine the impacts of disability onset on benefit receipt in Britain over the period 2004–2012. Differences in the timing of onset are exploited for identification in a framework that combines propensity score matching with difference-in-differences estimation. Disability onset increases receipt of disability insurance, a wider measure of sickness and disability benefits, and receipt of non-sickness benefits by six, eight and six percentage points respectively in the first year. These effects do not vary significantly by individual characteristics, but are larger for more severe disability onset, for those who did not previously report a long-term health condition, and for those who experienced disability onset under the less restrictive pre-2009 disability benefit regime. Contrary to the perception of disability benefits being an absorbing state, disability exit has an almost symmetrical impact on receipt of disability insurance and on wider sickness benefits in the first year.
Keywords: H51; H53; I38; J14; 330; disability; disability onset; disability exit; welfare benefits; disability insurance; propensity score matching